Optimization of Public Service Management at PT Endah Manunggal Persada Clinic Through Patient Satisfaction Information System Application (E-Sikap) - Pratiwi, Amelia Ika; Widhianningrum, Purweni; Subairi, Subairi (Journal of Innovation and Applied Technology, 2025)
This community service activity aims to develop strategies for improving service quality through the E-Sikap application at the PT. Endah Manunggal Persada Clinic. The method used in this community service activity is descriptive-qualitative. The results of the patient satisfaction survey in the registration and general examination units indicate that there are two elements that still have lower scores compared to the others, namely the suitability of service products and complaint handling. To address this matter, the management of the PT. Endah Manunggal Persada clinic must consistently uphold their commitment to providing healthcare services that are prompt, accurate, transparent, straightforward, easy to implement, and non-discriminatory.